The Challenges of Integrating Ukrainian Economic Migrants and Refugees in Poland - Sabina Kubiciel-Lodzińska; Brygida Solga (Intereconomics, 2023)
In a relatively brief timeframe, Poland has witnessed a substantial increase in immigration,transitioning from predominantly an emigration country to one characterised by both emigrationand immigration. Undoubtedly, with the outbreak of war in Ukraine, the need to implementintegration measures has become even more critical. However, the problem is that there isno system of coherent migration and integration policy at the national level, so the effort tointegrate foreigners, including refugees, is undertaken by individual Polish cities and regions.One of them is the Opolskie Voivodeship, a region with a high number of emigrants andtherefore deep demographic problems and labour market shortages. The article presents themost important conclusions and recommendations for regional policy on integrating foreigners.
Keywords: J1; J6; J18; 330; Refugees; migrants; migration policy; social integration; Poland; Ukraine; Flüchtlinge; Migranten; Migrationspolitik; Soziale Integration; Polen; Ukraine